Big data research is everyone's research—Making epilepsy data science accessible to the global community: Report of the ILAE big data commission - Josephson, Colin B.; Aronica, Eleonora; Beniczky, Sandor; Boyce, Danielle; Cavalleri, Gianpiero; Denaxas, Spiros; French, Jacqueline; Jehi, Lara; Koh, Hyunyong; Kwan, Patrick; McDonald, Carrie; Mitchell, James W.; et al. (Epileptic Disorders, 2024)
Epilepsy care generates multiple sources of high-dimensional data, including clinical, imaging, electroencephalographic, genomic, and neuropsychological information, that are collected routinely to establish the diagnosis and guide management. Thanks to high-performance computing, sophisticated graphics processing units, and advanced analytics, we are now on the cusp of being able to use these data to significantly improve individualized care for people with epilepsy. Despite this, many clinicians, health care providers, and people with epilepsy are apprehensive about implementing Big Data and accompanying technologies such as artificial intelligence (AI). Practical, ethical, privacy, and climate issues represent real and enduring concerns that have yet to be completely resolved. Similarly, Big Data and AI-related biases have the potential to exacerbate local and global disparities. These are highly germane concerns to the field of epilepsy, given its high burden in developing nations and areas of socioeconomic deprivation. This educational paper from the International League Against Epilepsy's (ILAE) Big Data Commission aims to help clinicians caring for people with epilepsy become familiar with how Big Data is collected and processed, how they are applied to studies using AI, and outline the immense potential positive impact Big Data can have on diagnosis and management.
CRIS-Team Scopus Importer:2024-11-01
Keywords: artificial intelligence; big data; common data models; epilepsy; ethics